An Analysis Of Politeness Strategies In Directive Speech Act Used By Main Characters In Green Book Movie - Restuadi, Yohan; Ardi, Havid (English Language and Literature, 2021)
This research aims at examining the types of directive speech act in the Green Book movie, and politeness strategies employed by the main characters. The purpose of this research is to find out the type of directive speech act used by main characters and what the types of politeness strategies used in directive speech acts as function in Green Book movie. The data were directive utterance that uttered by Tony Vallelonga and Dr. Donald Shirley and the source of the main data in this study was Green Book movie and its script. This research belonged to a descriptive-qualitative method. The results of the study show that there were five kinds of directive speech act and four types of politeness strategies. The amount totals of data are 163. In directive speech act, there are 39 data of commanding, 36 data of requesting, 56 data of questioning, 24 data of suggesting, and 8 data of forbidding. While in politeness strategies, they applied bald-on record 77 data, positive politeness 71 data, negative politeness 13 data and bald-off record 2 data. Directive speech act in the form questioning is commonly used by main character and bald on record is the mostly used in politeness strategy which is a strategy where the utterances are uttered clearly and concisely.